Dedicated Mobile Communications for High-speed Railway. (2017) - Zhong, Zhang-Dui; Ai, Bo; Zhu, Gang; Wu, Hao; Xiong, Lei; Wang, Fang-Gang; Lei, Lei, 1981-; Ding, Jian-Wen; Guan, Ke; He, Rui-Si
No abstract available